Laparoscopic dorsal subsegmentectomy 8: Exploit the 3d technology to plan liver resection, and predict intraparenchymal pedicles. A case report. (With video explanation). (November 2021) - Banchini, F.; Romboli, A.; Rizzi, N.; Luzietti, E.; Conti, L.; Capelli, P.
Abstract: Introduction: Laparoscopic liver surgery is spreading, encouraged by technical and technological improvement. Both the obligated narrow space and the difficulty to modify it lead to a more complex approach to the lesions located in the posterosuperior portion of the liver. Surgical strategies such as the Caudal approach or the Diamond technique could ameliorate surgical procedure, but these areas remain a challenge and are still classified as complex. Clinical case: We discuss the case of a 68 year old man with metachronous liver metastasis in the dorsal part of segment 8. We used portal phase CT-scan Dicom data to create Three-dimensional reconstruction, which was able to show the more distal branches of intraparenchymal structures. The reconstructed images were subsequently used to plan laparoscopic liver resection. Discussion: The capability of three-dimensional reconstruction to create a realistic image allows us to use ultrasound as a navigation tool. Exploiting these two technologies together, we arrived to regulate the resection stages by recognizing previously marked structures and searching them at every intervention phase. The strategy performed demonstrates both a high level of precision and the capability to predict intraparenchymal structures. Conclusion: The advantages obtained from three-dimensional reconstruction are numerous in terms of either anatomical comprehension and technical precision, suggesting a potential improvement in surgical skill. Three-dimensional technology should be encouraged and spread to understand, in every single aspect, the potential of its use. Highlights: Laparoscopic liver surgery of the posterosuperior segments remains a complex procedure. Patient-specific anatomy represents a pivotal point to perform precise and safe resections. Three-dimensional imaging is the simplest way to know the patient's anatomy, arranging the intraparenchymal structures with high precision. Three-dimensional technology in all its forms might become a helpful tool in planning and executing surgical interventions.